Kajian Pengaruh Lingkungan Terhadap Perilaku Bullying di Madrasah Ibtidaiyah - Frendiska Tiana; Aja Ardila Febriani; Serla Damayanti (CV. Master Literasi Indonesia, 2026)
this study aims to determine the influence of the environment on bullying behavior among students in Madrasah Ibtidaiyah. The environment has a major role in shaping children's behavior; if the environment is unfavorable, bullying may arise and negatively affect students' mental, social, and academic conditions. Therefore, it is necessary to examine how the environment contributes to the emergence of bullying behavior in elementary school-aged children. This study uses a qualitative approach with a literature review method. Data were obtained from various written sources such as books, scientific journals, news reports, articles, theses, and previous studies relevant to the research topic. The data analysis technique used involved collecting, reading, reviewing, and drawing conclusions from various theories and research findings regarding the influence of the environment on bullying behavior